Improving Teacher Performance Through Academic Supervision, Work Motivation, and Work Environment at MI (Madrasah Ibtidaiyah) and SD (Sekolah Dasar) Under the Guidance of PC LP. Ma'arif NU Pasuruan City - Alfian Darmawan , Mukhammad; Kartiko, Ari (Universitas Muhammadiyah Pontianak, 2026)
Teacher performance is a critical factor in improving educational quality, yet it remains a challenge in schools under PC LP Ma’arif NU Pasuruan City. This study examines the effects of academic supervision, work motivation, and work environment on teacher performance. Using a quantitative approach, data were collected from 81 MI and SD teachers and analyzed through multiple regression. The results indicate that academic supervision has a significant negative effect, while work motivation and work environment have significant positive effects on teacher performance. Simultaneously, all variables significantly influence performance, with work environment being the dominant factor. The findings highlight the importance of creating supportive working conditions to enhance teacher performance.